Phytochemical screening and evaluation of antioxidant, enzyme inhibition, anti-proliferative and calcium oxalate anti-crystallization activities of Micromeria fruticosa spp. brachycalyx and Rhus coriaria - ŞENKARDEŞ, İSMAİL; TAŞKIN, TURGUT (ELSEVIER, 2020)
Micromeria fruticosa spp. brachycalyx species (Lamiaceae) is used as a spice and flavoring agent. Rhus coriaria (Sumac) is widely used both spice and medicinally. In this study, antioxidant, anti-urease, anticholinesterase, anti-proliferative and calcium oxalate anti-crystallization activities of different extracts from M. fruticosa spp. brachycalyx aerial parts and R. coriaria leaves were investigated. Besides, the phytochemical content of these species was analyzed qualitatively and quantitatively. R. coriaria methanol extract showed stronger antioxidant (DPPH, FRAP, CUPRAC, ARTS) and anticholinesterase (46.85%) activity than M. fruticosa spp. brachycalyx extracts. M. fruticosa spp. brachycalyx methanol extract was found to have the highest anti-urease (11.39%) and anti-proliferative (MCF-7: 53.51%) potential. It was observed that the methanol extracts of both plants had a significant inhibition effect on calcium oxalate crystallization. R. coriaria methanol extract was determined to contain high amounts of total flavonoids (0.177 mgQE/mg extract) and tannins (0.365 mg TAE/mg extract) contents. The extracts from both plants have no cytotoxic effects on the healthy cell (L-929) and have strong biological activities in parallel with traditional use, suggesting that these plants may be used as natural sources in the future.
Keywords: M. fruticosa spp. brachycalyx; R.coriaria; Phytochemical contents; Biological activity; ESSENTIAL OIL; L.; EXTRACT; OSTEOPONTIN; POLYPHENOLS; CAPACITY; GROWTH